Do energy efficiency improvements reduce energy use? Empirical evidence on the economy-wide rebound effect in Europe and the United States - Anne Berner; Stephan B. Bruns; Alessio Moneta; David I. Stern (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2021)
Improving energy efficiency is often considered to be one of the keys to reducing greenhouse gas emissions. However, efficiency gains also reduce the cost of energy services and may even reduce the price of energy, resulting in energy use rebounding and potential energy use savings being eaten up. There is only limited empirical research quantifying the economy-wide rebound effect that takes the dynamic economic responses to energy efficiency improvements into account. We use a Structural Factor-Augmented Vector Autoregressive model (S-FAVAR) that allows us to track how energy use changes in response to an energy efficiency improvement while accounting for a vast range of potential confounders. Our findings point to economy-wide rebound effects of 78% to 101% after two years in France, Germany, Italy, the U.K., and the U.S. These findings imply that energy efficiency innovations alone may be of limited help in reducing future energy use and emphasize the importance of tackling carbon emissions directly.
Keywords: 330; Energy efficiency; economy-wide rebound effect; climate change; climate policy; Structural FAVAR; Independent Component Analysis